Ecotourism in Taman Negara National Park: issues and challenges - Samdin, Zaiton; Abdul Aziz, Yuhanis; Yacob, Mohd Rusli (Universiti Putra Malaysia Press, 2013)
Ecotourism is one type of tourism that promotes conservation and minimises visitor impacts. This exploratory study employed a semi-structured face-to-face in-depth interview. This study involved 9 visitors in Taman Negara National Park (TNNP). It was designed to identify recent issues and problems faced by the management of TNNP. Current issues and problems faced at the park, including pricing policy dilemmas and the current funding situation, were identified and also discussed. It was found that the main problem at TNNP rooted from inefficiency in pricing policy. Other problems included natural resource conflicts, visitor management and environmental degradation. It is therefore debatable that the main ingredient for the survival of TNNP is the commitment and participation of the stakeholders involved, which comprised of the government, the park authority, private sector, local community, etc.